ANALISIS PERTUMBUHAN DAN KONTRIBUSI RETRIBUSI PARKIR KENDARAAN BERMOTOR TERHADAP RETRIBUSI DAERAH KOTA JAMBI - Afrizal - (JURNAL AKADEMIKA)
In the average - average over the period 2001-2011 PAD Jambi City has experienced a growth of 26.74 percent . In the same period , the growth rate of the city of Jambi reception levies amounted to 22.81 percent . The growth rate of levy receipts parking fees in the city of Jambi increased by 11:23 persen.Kontribusi parking charges against region income amounted to 5.69 Jambi city . and in the s ame period of the parking levy contribution levies amounted to 11.68 percent .